The Political Economy of Inequality - Reformism or Socialism? - Stevenson, Paul (Labour / Le Travail, 2009)
The article reviews the book "Inequality and Prosperity: Social Europe vs. Liberal America," by Jonas Pontusson.
Keywords: BOOKS – Reviews; Equality; INEQUALITY & Prosperity: Social Europe vs. Liberal America (Book); Nonfiction; PONTUSSON; Jonas